Brand Satisfaction Toward Repurchase Intention With Affective Commitment And Continuence Commitment As Mediator Variables - Mahardika, Pamula, Dr. Agus Anton Setiawan, S.E., M.Si (2013)
The main purpouse of this study to examined the extent to which afective comitment and continuence commitmet serve as mediator of brand satisfactionrepurchase itention relationship. This study replicated from (Fullerton 2005) entitled the impact of brand commitmen on loyalty to retail service brands . As object of this study is . "NIKMAT RASA" The collected samples only reached 61 out of 100 sample spreaded and classified into gender,age, job and education level. This study found that both of mediators variables are partial mediation or not significantly mediated. Using hierachical regression analyisis.